Hybrid assessment of groundwater quality using fuzzy logic and conventional indices in Sidi Kada Mountains (Algeria) - Benadela, Laouni; Bekkousa, Belkacem (Journal of Degraded and Mining Lands Management, 2025)
Groundwater resources are vital for supplying drinking water in semi-arid regions, where limited and irregular precipitation makes surface water unreliable for both urban and rural communities. This study assessed the drinking water quality of the Jurassic aquifer in the Sidi Kada Mountains (northwestern Algeria) by integrating three classic groundwater quality indices: the Weighted Water Quality Index (WQI), the Analytic Hierarchy Process Water Quality Index (AHP-WQI), and the Entropy Water Quality Index (EWQI), with a Mamdani-type fuzzy inference system. The indices were calculated using major physico-chemical parameters from 26 boreholes. Although the WQI, AHP-WQI, and EWQI classified most sampling points as Good to Excellent, chloride and nitrate concentrations locally approached or exceeded WHO drinking water standards in several boreholes, indicating contamination risks. To address this limitation, the fuzzy system combined the three indices with nitrate and chloride concentrations as explicit corrective parameters, providing a more precautionary classification framework. In addition, the spatial distribution of the boreholes was examined using a land use/land cover (LULC) map to identify links between local exceedances and anthropogenic pressures. The results showed that while global index scores suggest generally safe water quality, five boreholes (19%) were ultimately classified as NonAcceptable for drinking. This integrated approach demonstrates that combining conventional indices with fuzzy logic and compliance checks improves the robustness and reliability of groundwater quality assessments in semi-arid aquifers. The findings offer practical guidance for water managers to select priority monitoring stations and secure a safe and sustainable drinking water supply for the region.